2015
DOI: 10.12659/pjr.895354
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal Diverticulosis Presented with Acute Abdomen and Diverticulitis Complication: A Case Report

Abstract: SummaryBackgroundJejunal diverticulosis is a rare, usually asymptomatic disease. Its incidence increases with age. If symptomatic, diverticulosis may cause life-threatening acute complications such as diverticulitis, perforation, intestinal hemorrhage and obstruction. In this report, we aimed to present a 67-year-old male patient with jejunal diverticulitis accompanying with abdominal pain and vomiting.Case ReportA 67-year-old male patient complaining of epigastric pain for a week and nausea and fever for a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Two cases required surgical therapy within 3 days, one case within about 1 month, and one case did not need surgery. Several earlier reports suggested that a conservative management may be sufficient to treat uncomplicated terminal ileum diverticulitis without perforation [ 8 , 9 ]. However, early surgical treatment represents the approach of choice for patients with confirmed diverticulitis and serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Two cases required surgical therapy within 3 days, one case within about 1 month, and one case did not need surgery. Several earlier reports suggested that a conservative management may be sufficient to treat uncomplicated terminal ileum diverticulitis without perforation [ 8 , 9 ]. However, early surgical treatment represents the approach of choice for patients with confirmed diverticulitis and serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, El-Haddawi and Civil presented a series of five patients with perforated diverticula in whom radiography was unremarkable [ 2 ]. However, the erect plain film of the abdomen can potentially give information about air or fluid levels, the presence of free air in the abdomen, and dilated intestinal loops [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients who develop severe epigastric pain, one must suspect incarceration and/or obstruction [ 11 ].…”
Section: Discussionmentioning
confidence: 99%